Oncologic considerations in the elderly. Issue 1 (February 2018) - Kamel, Mohamed K.; Port, Jeffrey L.
Abstract : Purpose of review: Elderly patients presenting with thoracic malignancies tend to be largely undertreated because of a presumption that this group will incur a high treatment-associated morbidity and mortality. The current review highlights the current practice and recent updates in the surgical management of thoracic malignancies, mainly lung cancer, in the elderly population. Recent findings: Lung resections appears to be relatively safe in the elderly patients presenting with lung cancer. Whenever possible, a lobectomy should be offered to patients with a good performance status who present with early stage disease. However, a limited resection may offer a valuable comparable alternative in patients with advanced comorbidities and borderline pulmonary functions. The use of minimally invasive approaches, namely video-assisted thoracoscopic surgery and robotic surgery are associated with lower morbidity and improved perioperative outcomes compared with the traditional thoracotomy approach and are ideal for the aged. In elderly patients presenting with advanced staged lung cancer, major lung resections following induction therapy, although feasible, should be discussed in a multispecialty tumor board committee. Summary: There is growing evidence from the literature that surgical resection is relatively safe in the elderly population. Age by itself should not preclude patients from having curative resection. Resections can be tailored to performance status of the patient.